The motor industry development programme and local content: has the MIDP's objective of increasing the local sourcing of components been achieved? - Bhanisi, Sipho (School of Economics, 2024)
The 1995 Motor Industry Development Programme (MIDP) was an attempt to transform the South African Automotive industry into a globally competitive industry. The import substitution policies, before the MIDP, which were characterised by high tariffs and local content requirements were ·replaced by an import-export complementation scheme, which encourages competitiveness by the introduction of foreign competition and assistance for exporting. This dissertation investigates whether the MIDP has increased value added or local content in locally manufactured motor vehicles, as anticipated by policy makers. The findings in this dissertation rely heavily on the limited data that is available in the industry. A dataset of component firms is used to establish the current trends with regard to local content in the domestic component industry. Export data is used to measure local content in both motor vehicles and component exports. Local content in the component purchases of the carmakers is also measured using a range of industry statistics. This dissertation shows that the domestic automotive industry has restructured and rationalised vehicle production, but despite this, local content in locally manufactured motor vehicles remains low. There appears to be a structural break between the domestic component industry and the vehicle· assembly industry. The South African component industry manufactures a large quantity of raw material intensive components that are targeted at foreign markets. In terms of the MIDP these exports can be used to offset import duties. The growing domestic vehicle production has to a significant effect been supplied by an increase of component imports. The major foreign owned component firms seem to be also involved in just-in-time assembling of these components for the carmakers. This is implied by the low levels of local content in their products.